2015
DOI: 10.15640/ijhs.v3n4a9
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Management and its Role for Health Benefits: Narrative Review

Abstract: In developed countries, modern conveniences and technology have contributed to increasing physical inactivity among adults. For example, World Health Organization (WHO) reported in 2008, 31% of adults exhibit a sedentary lifestyle, and have a 20-30% increased risk of mortality compared to active people. Therefore, increasing the level of physical activity to help them become more active, and hence reduce the burden of chronic diseases and improve health-related quality of life (HRQL) is considered important. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 89 publications
0
3
0
Order By: Relevance
“…For example, World Health Organization (WHO) reported in 2008, 31% of adults exhibit a sedentary lifestyle, and have a 20-30% increased risk of mortality compared to active people. Therefore, increasing the level of physical activity to help them become more active, and hence reduce the burden of chronic diseases and improve health-related quality of life (HRQL) is considered important [4].…”
Section: Resultsmentioning
confidence: 99%
“…For example, World Health Organization (WHO) reported in 2008, 31% of adults exhibit a sedentary lifestyle, and have a 20-30% increased risk of mortality compared to active people. Therefore, increasing the level of physical activity to help them become more active, and hence reduce the burden of chronic diseases and improve health-related quality of life (HRQL) is considered important [4].…”
Section: Resultsmentioning
confidence: 99%
“…In this research we found that there was a great problem about lesson students. In addition regular bodily endeavor is defined as "any bodily movement proved by way of the skeletal muscle these results in (Mansi & Khaldi, 2015) energy expenditure".…”
Section: Discussionmentioning
confidence: 99%
“…Undoubtedly, the growing popularity of this type of PA is associated with uncomplicated structure of movement that occurs during walking, as well as with the possibility of taking part it in a green environment. Current studies have shown that walking is a popular form of PA [ 6 , 7 ]. This is due to the fact that this form is comfortable and overcomes many widely perceived barriers to PA such as lack of time, lack of physical fitness or technical skills [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%